The End of the American Century - Mason, David S. (Rowman & Littlefield Publishers, 2008)
This compelling and persuasive book is the first to explore all of the interrelated aspects of America's decline. Hard-hitting and provocative, yet measured and clearly written, The End of the American Century demonstrates the phases of social, economic, and international decline that mark the end of a period of world dominance that began with World War II. The costs of the war on terror and the Iraq War have exacerbated the already daunting problems of debt, poverty, inequality, and political and social decay. David S. Mason convincingly argues that the United States, like other great powers in the past, is experiencing the dilemma of "imperial overstretch"—bankrupting the home front in pursuit of costly and fruitless foreign ventures. The author shows that elsewhere in the world, the United States is no longer admired as a model for democracy and economic development; indeed, it is often feared or resented. He compares the United States and its accomplishments with other industrialized democracies and potential rivals. The European Union is more stable in economic and social terms, and countries like India and China are more economically dynamic. These and other nations will soon eclipse the United States, signaling a fundamental transformation of the global scene. This transition will require huge adjustments for American citizens and political leaders alike. But in the end, Americans—and the world—will be better off with a less profligate, more interdependent United States. More information is available on the author's website.